Studies of wafer level electromigration test for ULSI - Sum, Heng Keong. (2008)
Microelectronic test structures are used for wide variety of tasks which include equipment characterizations, reliability evaluations, defect monitoring, transistor parameter extraction and process verification and development. Similarly, test structures are used in electromigration evaluation. In this dissertation, the various common test structures used in electromigration test were reviewed. The structures’ application, advantages and disadvantages were discussed.